Consumer Dispute Resolution - Danang Dermawan (Program Pascasarjana UIN Sumatera Utara Medan, 2026)
Consumer disputes arise when consumers suffer losses due to violations of their rights by business actors in the provision of goods and services. Although litigation remains a formal mechanism for dispute resolution, court proceedings are often considered time-consuming, costly, and less effective in maintaining the relationship between the disputing parties. Consequently, Indonesian consumer protection law recognizes non-litigation dispute resolution as an alternative mechanism that emphasizes efficiency, fairness, and consensus. This study aims to examine the implementation of non-litigation consumer dispute resolution in Indonesia and to analyze the role of the Consumer Dispute Settlement Agency (Badan Settlement Disputes Consumer/BPSK) in resolving disputes between consumers and business actors. The research employs a normative juridical method using a statutory and conceptual approach. Data were collected through library research by analyzing legislation, legal doctrines, and relevant scholarly literature concerning consumer protection and alternative dispute resolution. The findings indicate that BPSK serves as a specialized institution authorized to resolve consumer disputes through mediation, arbitration, and conciliation. These mechanisms provide several advantages, including faster procedures, lower costs, confidentiality, procedural flexibility, and the preservation of harmonious relationships between the parties. The study further reveals that BPSK plays a significant role in ensuring access to justice for consumers while promoting legal certainty and encouraging business actors to conduct their commercial activities responsibly. Nevertheless, the effectiveness of non-litigation dispute resolution remains dependent upon the willingness of the parties to participate in good faith and comply with the resulting agreements or decisions. Therefore, strengthening the institutional capacity of BPSK and increasing public awareness of consumer rights are essential to enhancing the effectiveness of consumer protection in Indonesia.